TANGGUNG JAWAB NOTARIS TERHADAP PEMBATALAN AKTA WASIAT YANG BAGIANNYA MELEBIHI KETENTUAN HUKUM ISLAM (STUDI PUTUSAN NO. 0731/PDT.G/2013/PA.RBG) - TUTINING RHOMLAH (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. H. Hasballah Thaib2. Utary Maharany Barus3. Idha Aprilyana Sembiring A will is a statement written by a person who wants to give his property to someone else after he dies. It is stated in the Civil Code and KHI (Compilation of the Islamic laws) that the testator is allowed to distribute only one third of his property to protect his heir. The research used juridical normative method. The research used descriptive analytic method The result of the research, based on the Civil Code, Chapter XIII, Book Two, Article 874 until Article 912. Article 194 until Article 209 of KHI states that a Notary is required to ask the testator in a written Deed whether the property belongs to him as stipulated in Article 194, paragraph 2 of KHI, whether the other heirs have agreed, and only one third of the property which is allowed to be given as it is stipulated in Article 195, paragraph 2 of KHI. The Plaintiff has made LL binti Y, a 17 year-old girl as the Defendant III as it is stipulated in Article 330 of the Civil Code in conjunction with Article 68, paragraph 1 of KHI since she is not an adult yet. When the property is the inheritance controlled by defendants, it becomes a dispute in ownership. Based on this consideration, the plaintiff’s claim is obscure (obscuur libel); therefore, the case is not accepted (niet onvankelijke verklaart).Keywords: Notary’s Liability, Revocation of Will, Exceeding Regulation